Implementation of Sharia Economic Principles in SMEs: Prescription of Challenges and Opportunities in the Era of the Global Halal Industry - Saiful Arif; Tatha Amelia Fretika; Devi Triana; Lailatul Fitria; Muhammad Ersya Faraby (Penerbit Hellow Pustaka, 2025)
This study aims to provide a prescriptive framework for implementing Islamic economic principles among Small, and Medium Enterprises (SMEs) in addressing challenges and opportunities within the era of global halal industry. Using a qualitative descriptive approach based on literature review, this research examines the relevance of core Islamic economic values such as justice (‘adl), trustworthiness (amanah), public interest (maslahah), and transparency in strengthening the global competitiveness of MSMEs. The findings reveal that the application of Islamic economic principles has significant potential to enhance business sustainability and increase consumer trust in halal products. However, empirical evidence indicates that implementation remains constrained by limited Islamic financial literacy, weak halal value chain integration, and restricted access to sharia-based financing. Therefore, this study recommends strategic collaboration among governments, Islamic financial institutions, and halal business incubators to build an SME ecosystem that upholds Islamic values while remaining adaptive to global economic developments.